The 5‐lipoxygenase‐activating protein inhibitor, GSK2190915, attenuates the early and late responses to inhaled allergen in mild asthma. Issue 2 (18th January 2013) - Kent, S. E.; Boyce, M.; Diamant, Z.; Singh, D.; O'Connor, B. J.; Saggu, P. S.; Norris, V.
Summary: Background: GSK2190915, a potent 5‐lipoxygenase‐activating protein inhibitor, prevents the synthesis of leukotrienes and 5‐oxo‐6, 8, 11, 14‐eicosatetraenoic acid (5‐oxo‐ETE). Objective: To assess the effect of GSK2190915 on the allergen‐induced asthmatic responses. Methods: Nineteen eligible male subjects with mild asthma were enrolled in and completed this four‐centre, double‐blind, two‐way crossover study (ClinicalTrials.gov NCT00748306). Subjects took GSK2190915 100 mg and placebo orally once daily for 5 days in randomized order. On Day 1 and 4 they had a methacholine challenge, on Day 3 they had an inhaled allergen challenge, and on Days 4 and 6 they had sputum induction. Results: GSK2190915 attenuated the early (0–2 h) and late (4–10 h) asthmatic responses to inhaled allergen compared with placebo. There was a statistically significant attenuation of the early asthmatic response (EAR) by GSK2190915; treatment difference of GSK2190915 vs. placebo for the minimum FEV1 EAR was 0.408 L (0.205, 0.611). There was a statistically significant attenuation of the late asthmatic response (LAR) by GSK2190915; the treatment difference of GSK2190915 vs. placebo for the minimum FEV1 LAR was 0.229 L (0.041, 0.417). There was a statistically significant attenuation of allergen‐induced sputum eosinophil count on Day 4 following GSK2190915: mean treatment difference (95% CI) between GSK2190915 and placebo was −9.95% (−18.15%, −1.77%). Compared with placebo, GSK2190915 100 mg reduced median sputum LTB4 by > 90% on Days 4 and 6. There was no effect on methacholine PC20 post allergen. GSK2190915 was generally well tolerated. Conclusion and Clinical Relevance: GSK2190915 shows potential as a treatment for patients with asthma.